Depression in midlife women attending a menopause clinic is associated with a history of childhood maltreatment. (4th March 2022) - Shea, A. K.; Frey, B. N.; Gervais, N.; Lopez, A.; Minuzzi, L.
Abstract: A growing body of literature has suggested that the perimenopause and the early postmenopausal years are associated with an increased risk of experiencing symptoms of depression and the development of first-onset and recurrent episodes of major depressive disorder. Multiple risk factors have been identified, including stressful life events and lower socioeconomic status, as well as early life adversity. The objective of the current study was to characterize the influence of early life childhood maltreatment and incident depression among women experiencing bothersome menopausal symptoms. Participants were recruited from two university-affiliated specialty clinics caring for women with bothersome menopausal symptoms. Assessments included the Childhood Trauma Questionnaire (CTQ), the Center for Epidemiological Studies – Depression (CES-D) scale and the Greene Climacteric Scale. Findings from this cross-sectional study indicate that adverse childhood experiences, as measured using the CTQ, were highly prevalent among women seeking care for bothersome menopausal symptoms (66%). Further, a greater score on the CTQ was significantly associated with higher CES-D scores, as well as with a greater burden of menopausal symptoms, after adjusting for confounding. Our findings lend support to the growing body of literature suggesting that early life stress affects mental health well into adulthood.